Possibilidades da utilização da massagem no tratamento de indivíduos com doença de Parkinson e suas implicações na mobilidade funcional: revisão de literatura - FRANÇA, Simone Aragão (2023)
Parkinson's disease, being a neurodegenerative disease, implies progressive losses in the life of its patients, among them the one of the functional mobility, causing a sudden change of habits in its occupational routine. This study aims to carry out a survey of scientific articles that use therapeutic massage as a complementary resource in the treatment of PD and its repercussions on the performance of mobility. The present study is an integrative review of the literature. After reading 18 articles, 11 publications that did not fit the established context were discarded. Thus, 8 articles were included in this review because they fit the inclusion criteria of this study. Although it is already a technique recommended by the legislature and is widely used in the context of primary care, there is still insufficient evidence of the use of massage techniques in the treatment of PD. Finally, we emphasize and confirm that this research developed by the authors becomes an incentive for future research, in the improvement of the validity of our professional practice, by the intersections of massage and Occupational Therapy.